De Novo Assembly and Annotation of the Larval Transcriptome of Two Spadefoot Toads Widely Divergent in Developmental Rate. Issue 8 (1st August 2019) - Liedtke, H Christoph; Garrido, Jèssica Gómez; Esteve-Codina, Anna; Gut, Marta; Alioto, Tyler; Gomez-Mestre, Ivan
Abstract: Amphibians are highly vulnerable and diverse vertebrates for which we still have modest genomic resources. Amphibian larvae are key components of continental wetlands, where they have strong influences on energy fluxes, nutrient cycling, and community structure. Amphibian larvae are highly sensitive to environmental conditions and can often alter their physiology, behavior and even morphology in response to the local conditions experienced, although we still know relatively little about the transcriptomic changes that enable such plasticity. Here we contribute the larval transcriptomes of two spadefoot toad species with divergent developmental rates and degree of developmental plasticity in response to pond drying.